PENGARUH ISLAMIC GAMES DALAM MENGEMBANGKAN NILAI AGAMA ANAK USIA DINI DI ERA PANDEMI COVID-19 - Dita Primashanti Koesmadi (Universitas Islam Lamongan, 2021)
This study contains about the application of islamic games in developing the religious value of early childhood in the era of pandemic covid-19. This type of research method uses experimental research with design that is experimental design with non-equivalent type control group design. This research was conducted in November to December 2020 with subjects is children aged 4-5 years in Purwosari Village, Kwadungan Subdistrict, Ngawi Regency with a total of 14 research subjects. The indicators of judgment in this assessment are (1) knowing the religion they follow, (2) praying before and after doing activities, (3) knowing God and His Creation, (4) distinguishing good and bad behavior, (5) imitating the movement of worship in the right order. The results of this study were in the control group obtained an average value (mean) pretest 1.28 and posttest 1.42, t paired t-test value as much as -2,534. While in the experimental group obtained an average value (mean) of 1.42 in the pretest and posttest 3.28. The t paired t-test value is -12,790. From the results of both groups (control and experimentation) obtained t independt t-test value of -11,277 and significance value of 0.000 So it can be said that the application of islamic games is able to develop the religious value of early childhood (4-5 years) is significantly.